Using Democratic Deliberation to Engage Veterans in Complex Policy Making for the Veterans Health Administration - Caverly, Tanner J. (Fed Pract, 2020)
A democratic deliberation panel of veterans providing insight into veteran perspectives on resource allocation and the Veterans Choice Act showed the importance and feasibility of engaging veterans in the policy-making process.